Comparing Fetal Weight Estimates in the Third Trimester: Clinical Examination Findings, Ultrasonographic Estimation, and Actual Birth Weight - Ayesha Ghaffar; Sabeen Ashraf; Hafiza Alia Akbar Khan; Saba Yousaf; Tallat Farkhanda; Amartur Rabbal (Journal of Rawalpindi Medical College)
Objective: To determine the relationship between fetal weight on clinical and ultrasonographic examinations and actual birth weight during the third trimester of pregnancy.